AN ERROR ANALYSIS OF GRAMMATICAL FEATURES IN REPORT TEXT BY THE ELEVENTH GRADE STUDENTS OF ACCOUNTING MAJOR AT SMK N 1 JORLANG HATARAN - Nomita Herlina Manurung and Willem Saragih (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2017)
This study is purposed to describe the errors in grammatical features of report text. In addition, this study is also aimed to describe the possible causes of those errors. This study applied the descriptive qualitative approach in which the data was obtained from the report texts that were written by the eleventh grade students of accounting major in SMK N 1 Jorlang Hataran. The data were collected by using students’ report texts and questionnaires. The data then were analyzed by identifying the errors first, then describing the errors, and the last explaining the errors. The errors that occurred in students’ texts are errors in verbs, sentences, prepositions, articles, agreements, pronouns, modifiers, and tenses. The result of the study indicates that the students made 541 grammatical errors which were classified into: 37,15% errors in verbs, 18,85% errors in noun, 15,15% errors in sentence, 11,27% errors in preposition, 7,76% errors in article, 4,06% errors in pronoun, 3,51% errors in modifier, and 2,21% errors in tenses. The students’ errors were caused by 31,23% ignorance of grammatical rules, 28,09% incomplete application of rules, 15,89% false concept hypothesized, 13,86% interference of interlingual transfer, 9,05% wrong communication strategy, 1,84% over-generalization.